Perioperative targeted temperature management of severely burned patients by means of an oesophageal temperature probe. Issue 2 (March 2023) - Furrer, Florian; Wendel-Garcia, Pedro David; Pfister, Pablo; Hofmaenner, Daniel Andrea; Franco, Carlos; Sachs, Alexandra; Fleischer, Juliane; Both, Christian; Kim, Bong Sun; Schuepbach, Reto A.; Steiger, Peter; Camen, Giovanni; et al.
Abstract: Background: Hypothermia in severely burned patients is associated with a significant increase in morbidity and mortality. The use of an oesophageal heat exchanger tube (EHT) can improve perioperative body temperatures in severely burned patients. The aim of this study was to investigate the intraoperative warming effect of oesophageal heat transfer in severe burn patients. Methods: Single-centre retrospective study performed at the Burns Centre of the University Hospital Zurich. Between January 2020 and May 2021 perioperative temperature management with EHT was explored in burned patients with a total body surface area (TBSA) larger than 30%. Data from patients, who received perioperative temperature management by EHT, were compared to data from the same patients during interventions performed under standard temperature management matching for length and type of intervention. Results: A total of 30 interventions (15 with and 15 without EHT) in 10 patients were analysed. Patient were 38 [26−48] years of age, presented with severe burns covering a median of 50 [42−64] % TBSA and were characterized by an ABSI of 10 [8−12] points. When receiving EHT management patients experienced warming at 0.07 °C per minute (4.2 °C/h) compared to a temperature loss of − 0.03 °C per minute (1.8 °C/h) when only receiving standard temperature management (p < 0.0001). No adverse or serious adverse events were reported. Conclusion: The use of an oesophageal heat transfer device was effective and safe in providing perioperative warming to severely burned patients when compared to a standard temperature management protocol. By employing an EHT as primary temperature management device perioperative hypothermia in severely burned patients can possibly be averted, potentially leading to reduced hypothermia-associated complications. Highlights: EHT was associated with intraoperative warming as opposed to standard temperature management. This study shows that the use of an EHT was effective and safe. EHT can potentially leading to reduced hypothermia-associated complications.